1991
DOI: 10.1021/je00002a009
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of binary mixtures containing organic carbonates. 4. Liquid-liquid equilibria of dimethyl carbonate + selected n-alkanes

Abstract: Liquid-liquid equilibrium (LLE) data are reported for dimethyl carbonate + n-decane, + n-dodecane, + n-tetradecane, or + n-hexadecane at atmospheric pressure, between 277 K and the upper critical temperatures. The solubility curve of pure solid n-hexadecane In liquid dimethyl carbonate Is also presented. The coexistence curves are very asymmetrical with respect to mole fraction, the asymmetry Increasing with the size of the n-alkane The critical solution points vary almost linearly with the number of carbon at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
32
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 7 publications
15
32
1
1
Order By: Relevance
“…A similar trend is encountered for many other mixtures. [21][22][23][24][25]35,37,38,[40][41][42][43] For a fixed n-alkane, we note that UCST (DMA) < UCST (DMF). That is, dipole-dipole interactions between amide molecules are stronger in the case of the DMF.…”
Section: Discussionmentioning
confidence: 79%
“…A similar trend is encountered for many other mixtures. [21][22][23][24][25]35,37,38,[40][41][42][43] For a fixed n-alkane, we note that UCST (DMA) < UCST (DMF). That is, dipole-dipole interactions between amide molecules are stronger in the case of the DMF.…”
Section: Discussionmentioning
confidence: 79%
“…for {dimethyl carbonate + C n H n+2 (n = 10, 12, 14, and 16)} can be found in the literature. (8) The critical temperatures T c and critical compositions x c were found to vary almost linearly as the length of the alkane chain increases, therefore, the critical co-ordinates of (dimethyl carbonate + n-heptane), T c = 267 K, x c = 0.59, were estimated from extrapolation of the available data. Thus, the highly temperature-dependent peaks of (dimethyl carbonate + n-heptane) are due to a non-random character of the mixture in the proximity of the u.c.s.t.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies dealt mainly with the composition dependence of the excess molar volume V E m , (1)(2)(3) excess molar enthalpy H E m , (4,5) and excess molar Gibbs energy G E m (6,7) at the temperature 298.15 K, and at atmospheric pressure. González et al (8) reported (liquid + liquid) equilibrium data (l.l.e.) for dimethyl carbonate with several n-alkanes and found their upper critical solution temperatures (u.c.s.t.)…”
Section: Introductionmentioning
confidence: 99%
“…[20]. Due to the known influence of impurities on the critical temperature [21], T c were experimentally determined from turbidity measurements, obtaining T c = 293.41 ± 0.01 K for dimethyl carbonate + undecane and T c = 298.62 ± 0.01 for dimethyl carbonate + dodecane.…”
Section: Methodsmentioning
confidence: 99%